If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -12 = 2x + 8 Reorder the terms: -12 + -2x = 2x + 8 Reorder the terms: -12 + -2x = 8 + 2x Solving -12 + -2x = 8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -12 + -2x + -2x = 8 + 2x + -2x Combine like terms: -2x + -2x = -4x -12 + -4x = 8 + 2x + -2x Combine like terms: 2x + -2x = 0 -12 + -4x = 8 + 0 -12 + -4x = 8 Add '12' to each side of the equation. -12 + 12 + -4x = 8 + 12 Combine like terms: -12 + 12 = 0 0 + -4x = 8 + 12 -4x = 8 + 12 Combine like terms: 8 + 12 = 20 -4x = 20 Divide each side by '-4'. x = -5 Simplifying x = -5
| 3.3=4.9-0.2x | | 2x+15=7x-5 | | 8x-5x+7x=30 | | 3(x-20)=100 | | 13=4*-9 | | (m+3n)(6m-5n)=0 | | x-(3x+7)=-5 | | x=24x^3-28x^2+8x | | 5x+y+0=3 | | 1=-0.25n+1 | | 5x-3(x-3)=-17 | | (x-8)+(5x)=(9x-80) | | 14=5n+4+5n | | 7(x+5)+6(x-1)=-10 | | 3.9-30= | | X-4-20x=-2 | | 6x^2-4x-20=14 | | X+3*4= | | X^2+13x+36=36 | | 54=27x | | 2x-4+12=8(x+1-2x) | | 45/(4+1)=18-49*(3+2) | | 5x+y+3=3 | | 4t^2-4t-8=0 | | 2y+x=110fory | | c=5a+b | | 2(x+6)=4(x+2.6) | | x-.4=.4x | | 45/(4+1)= | | -4(5a-10)=0 | | f(x)=27x | | 60c-54c+108=0 |